Clinical Trial Simulation in Geographic Atrophy: Patient, Caregiver, and Trial Site Staff Perspectives - Ivana Gunderson; Asma Burale; Bill J. Best; Cynthia I. Tung; Jochen Huber; Lisa Marsh (Ophthalmology and Therapy)
Abstract Introduction The perspectives of patients with geographic atrophy (GA) should be considered when planning new clinical trials to ensure that real-world patient needs are addressed. The purpose of this study was to explore the perspectives of patients, caregivers, and trial site staff on designing and planning a phase 2 clinical trial in GA. Methods This cross-sectional study included patients with GA and their caregivers, trial site staff, and investigators from Germany, the UK, and the USA. Participants were asked to spend 30 min reviewing a simulated trial design communicated as a simple video animation with a voiceover. Subsequently, a 90-min web-assisted telephone interview and survey was conducted to identify problems with the design of the simulated trial and explore potential solutions and improvements. Results Patients (n = 11), caregivers (n = 11), and site staff (n = 16) completed the survey after reviewing the simulated trial design. Survey responses suggested that study recruitment could be facilitated via widespread advertisement and by including a short washout period, i.e., the time period during which patients receive no medication prior to commencing the study drug to ensure that other treatments do not impact the study results. Survey suggestions for reducing the burden of trial participation included minimizing the number and frequency of trial visits, enabling assessments to be completed at home, and making the schedule of trial visits flexible. Appropriate investment in study center facilities was recommended. In addition, survey respondents proposed that providing transport could be highly beneficial, potentially enabling patients and caregivers to attend trial visits more easily. Conclusions This study provides valuable information on the viewpoints of patients, caregivers, and trial site staff regarding trial design. Accounting for these perspectives when designing future clinical trials may help ensure successful trial completion and promote positive perceptions of clinical research.